2015
DOI: 10.1002/ange.201507352
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Corrosion Triggered Spontaneous Generation of H2O2 on Oxidized Titanium for Promoting Angiogenesis

Abstract: Although the use of reactive oxygen species (ROS) has been extensively studied, current systems employe xternal stimuli such as light or electrical energy to produce ROS,which limits their practical usage.Inthis report, biocompatible metals were used to construct anovel electrochemical system that can spontaneously generate H 2 O 2 without any external light or voltage.T he corrosion of Mg transfers electrons to Audecorated oxidized Ti in an energetically favorable process, and the spontaneous generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This goal could also be achieved by Mg for its modulating microvascular functions in vivo [ 11 ]. Specifically, Mg-doped materials have proven to own enhanced angiogenic property in recent years, such as stimulating the production of reactive oxygen species, upregulating immune responses or promoting VEGF expression in human endothelial cells [ 12–14 ]. As a result, they have also been applied in vivo and achieved satisfying outcomes of vessel formation in animal models [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This goal could also be achieved by Mg for its modulating microvascular functions in vivo [ 11 ]. Specifically, Mg-doped materials have proven to own enhanced angiogenic property in recent years, such as stimulating the production of reactive oxygen species, upregulating immune responses or promoting VEGF expression in human endothelial cells [ 12–14 ]. As a result, they have also been applied in vivo and achieved satisfying outcomes of vessel formation in animal models [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown to have a limit of detection of 1 μM, which means that it is suitable for applications where μM concentrations of H 2 O 2 are expected. It is likely that cathodic stimulation of metals like titanium will result in μM levels of H 2 O 2 generation (Park et al, 2015). It was found that the sensitivity of the electrode was strongly influenced by the distance of the reference electrode from the sensing electrode.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ROS has drawn considerable attention for its wound healing-related efficacy as a mediator of angiogenesis [28][29][30][31]. Thus, efforts to utilize ROS for biomedical applications were actively directed at introducing diverse ROS generation strategies such as natural release from donor materials [23,[32][33][34], external electric/photonic stimuli [35][36][37], and electrochemical reaction [38]. Indeed, we previously reported the promotion of angiogenesis induced by electrochemically generated hydrogen peroxide (H 2 O 2 ), one of the typical endogenous ROS [38] [23,[29][30][31], their practical use in biomedical applications has not been sufficiently developed due to the difficulties associated with establishing an appropriate storage/delivery system in vivo.…”
Section: Introductionmentioning
confidence: 99%